Associations of healthy lifestyle and accelerated aging with incident breast cancer in pre- and postmenopausal women: a population-based cohort study - Wenyi Liu; Mengqing Yan; Zhixing Fan; Zhongli Ma; Yuanhang Zhu; Hui Chang; Ruoxin Jiang; Chenchen Ren (Scientific Reports)
Abstract Breast cancer is one of the most common malignancies in women. This study aimed to explore the association between healthy lifestyle, biological aging and breast cancer risk in pre- and postmenopausal women. This study included 125,579 participants. Biological aging was calculated using the PhenoAge algorithm. Cox regression models and counterfactual mediation analysis was utilized. During an average follow-up of 13.65 years, 5418 breast cancers occurred. In the overall women participants, compared to the healthy lifestyle group, the HR (95% CI) for unhealthy lifestyle regarding incident breast cancer was 1.28 (1.13, 1.33). Compared to the lowest tertile of accelerated aging (AA), the HR (95% CI) for the highest tertile regarding breast cancer risk was 1.22 (1.14, 1.30). Consistent results observed only in postmenopausal participants. The joint effect of a healthy lifestyle and AA on breast cancer risk was statistically significant (P < 0.001). The AA-mediated breast cancer risk ratio was 17.69 (95% CI 8.19, 27.19) when comparing healthy to unhealthy lifestyles. In the study, healthy lifestyle and lower levels of AA were significantly associated with a reduced risk of breast cancer, particularly among postmenopausal women. In addition, AA mediated 17.02–17.69% of the link between lifestyle and breast cancer risk.